The Representation Of Women's Empowerment In Song Lyrics On Yura Yunita Tutur Batin Album: Representasi Pemberdayaan Perempuan Dalam Lirik Lagu Pada Album Tutur Batin Karya Yura Yunita - Mutia Rastiwi; Isnaini Leo Shanty; Dody Irawan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to describe the representation of women's empowerment in song lyrics on Yura Yunita's album Tutur Batin. This album was selected because it addresses themes of self-acceptance, emotional strength, and women's struggles against patriarchal norms. The research employs a descriptive qualitative approach with a feminist literary criticism perspective. The data, consisting of song lyrics, were analyzed based on aspects of women's empowerment including self-awareness, control over life, courage in decision-making, and efforts to resist social standards that limit women. Data collection techniques utilized documentation study, while data analysis involved data reduction, data presentation, and conclusion drawing. The research findings indicate that the song lyrics in the Tutur Batin album represent women's empowerment through reflective narratives, self-affirmation, and strengthening of women's identity as empowered and emotionally independent individuals. Women's empowerment is portrayed through processes of self-acceptance, emotional healing, and rejection of unjust social demands. This research contributes to feminist literary studies and broadens understanding of music as a medium for advocacy and representation of women's empowerment.